MUTU ASPAL BETON PADA RUAS JALAN BLONDO-MENDHUT - Subagyo, Singgih (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The Blondo-Mendut road section is part of the Borobudur National Tourism Strategy Area as the main access to Borobudur Temple tourism destinations and its surroundings, making this road very vital. In the implementation of construction work, quality aspects are targeted in addition to timeliness and cost. Quality control is very important so that at every stage of work can be monitored so that the construction produced is according to predetermined specifications. The study aims to determine the quality of each stage of asphalt concrete work in the laboratory and field and to analyze the results of testing the asphalt concrete pavement layer according to the 2018 Bina Marga technical specification standards. From the results of asphalt concrete testing on the Blondo-Mendut Road Section Rehabilitation project at the Borobudur Magelang KSPN as follows: From the results of examining the aggregates from ex Clereng Kulonprogo, it was found that the average wear and tear was 19.40%, on crushed stone with a diameter of 0.5 max 3/8" the specific gravity of bj (bulk) was 2.57, bj surface saturated (SSD) was 2.64 and aggregate absorption (absorption) 2.95; crushed stone diameter 1-1 max 1/2” bj (bulk) 2.64 , surface saturated bj (SSD) 2.68 , and absorbtion 1.60; crushed stone with a diameter of 1-2 max 3/4” bj (bulk) 2.57, bj surface saturation (SSD) 2.61, and absorbtion 1.70. From the results of mixing the aggregate for the ACWC mixture consisting of 20% crushed stone (BP) 1-1 as much as 20%, crushed stone (BP) 0.5 as much as 30% and 50% ash, a gradation was obtained with the proportion of aggregate CA 52.8%, aggregate FA 40.7% and FF aggregate as much as 6.5%. From the JMD results obtained for the ACWC asphalt concrete mixture obtained marshall parameters with mixed asphalt content of 5.90%, asphalt absorption of 0.88% (<1.2%), voids in the mixture (VMM) 4.5% (limit 3-5 %), voids in mineral Aggregate (VMA) 15.9 % (>15%) , voids filled with bitumen (VFB) 72.0% (>65%) , stability 930 kg (>800 kg), density 2.341 ton/m2 , fatigue (flow) 3.20 mm (2-4 mm), and quotient (Marshall quantient) 310 kg/mm ​​(> 250 kg/mm). Field test results at 20 ACWC Asphalt Concrete Layer core drill points obtained an average thickness of 5.4 cm (> 4.0 cm), bulk density 2.293, density 98.62% (> 98%), and asphalt content 5.90 % who meet the requirements according to the 2018 General Highways Specifications.